PENGARUH RESTAURANT ATMOSPHERE DAN PERCEIVED VALUE TERHADAP CUSTOMER BEHAVIORAL INTENTION PADA RESTO SEAFOOD SITUBONDO - Maimuna, Riski; Suhartono, Suhartono; Khristianto, Wheny (Jurnal Bisnis dan Manajemen (JBM), 2023)
The high growth of restaurants has an impact on tight business competition. It gives the Situbondo Seafood restaurant the right marketing strategy and can influence customer behavior intentions. The appearance of a modern restaurant based on customers' wishes and needs impacts customer behavior intentions that can benefit the company. This study aims to analyze the effect of restaurant atmosphere and perceived value on customer behavior intentions and identify the most dominant variable influencing customer behavior intentions in Situbondo Seafood restaurant. This research method uses a quantitative approach with associative techniques. Data collection used a non-probability sampling technique with a purposive sampling sample through a questionnaire filled out by 130 Situbondo Seafood restaurant consumers. The results of the partial test of this study indicate that restaurant atmosphere has a significant positive effect on customer behavioral intention, and perceived value also has a significant positive effect on customer behavioral intention. Meanwhile, simultaneously, the atmosphere of the restaurant and perceived value have a significant positive effect on customer behavioral intention. Keywords: restaurant atmosphere, perceived value, customer behavioral intention